(untitled) (Journal of the Professional Association for Cactus Development, 2003)
Cold damage of Opuntia ellisiana plants obtained by micropropagation was estimated visually after 1- and 2-year growth periods in field conditions. Additionally, the effect of irrigation on above-ground biomass production was evaluated after a 2-year growth period and some parameters related to the nutritional quality of 1-year-growth-period cladodes were determined. Frost damage was estimated visually. Above-ground biomass and stem-area index (SAI) were estimated by regression techniques. One-year-growth plants suffered no frost damage when temperatures dropped to -15°C on two occasions in the winter of 2000. Frost damage reached only 0.9% in 2-year-growth-period plants after freezes of -14.5°C and -13.7°C in the winter of 2001. Irrigation did not have a significant effect on above-ground biomass production. Mean biomass reached 170 kg DM ha-1 after the 2-year growth period. This low production could be explained mainly by the small size of the plant material used for establishing the plantation and the low SAI after the 2-year growth period (0.03). Cladodes of O. ellisiana exhibited crude protein and organic-matter contents of 5.8% and 82.7%, respectively, and an in vitro dry-matter digestibility of 78.3%. Plants of O. ellisiana obtained by micropropagation appear to be tolerant to freezing temperatures attained in areas with extremely cold winters.